Approach to contraception in the primary health care: barrier, behavioral and pharmaceutical methods - Baoum, Shada Omar; Almomen, Zainab Abduljabbar; Alotaibi, Fatmah Abdullah; Almohaiya, Rawan Ayedh; Alharbi, Amani Abdullah; Hejazi, Hamed Arif; Alsabei, Hibah Abdullah; Algethami, Norah Salem; Shamlan, Nareman Sulaiman; Aljohani, Norah Dakhilallah; Alqahtani, Nura Ayidh (International Journal Of Community Medicine And Public Health, 2021)
Contraception is a critical tool in achieving favorable family planning, which has been reported with remarkable outcomes on the individual and country-based levels. Using contraceptive approaches has been reported to be cost efficacious with minimal side effects. It gives couples more freedom, privacy and control over their lives, which might also enhance the quality of life of these individuals. In the present study, we have reviewed evidence from current studies in the literature about the different approaches to contraception in primary care. We have discussed the different barrier and non-barrier approaches that have been validated in the literature as efficacious approaches that can achieve contraception. We also reviewed the safety profiles for the different modalities and whether they can be used or not. Overall, couples should consult with the primary care physician before approaching any modality to give them a better judgment about the potential benefits and risks of each suitable contraception tool. We suggest that educational campaigns should also be conducted to increase awareness and attitude about family planning and using contraceptive modalities to expand the application and favorable outcomes of using these tools.